2021
DOI: 10.3390/en14092483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tank and Battery Storages for Photovoltaic Water Pumping

Abstract: Photovoltaic water pumping systems (PVWPS) are a promising solution to improve domestic water access in low-income rural areas. It is challenging, however, to make them more affordable for the local communities. We develop here a comparative methodology to assess relevant features of both widely employed PVWPS architecture with water tank storage, and hardly used PVWPS architecture with a battery bank instead of tank storage. The quantitative comparison is carried out through techno-economic optimization, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The use of batteries in photovoltaic water pumping systems (PVWPS) presents some disadvantages, such as increased cost and reduction of efficiency [6] [7], and there are several studies cited in [8] [9] in which batteries are considered. A PVWPS in Oman incorporating a PV field with 840 W pk , no tank, and a 220 Ah lead-acid battery was the best solution analyzed after several simulations with HOMER [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of batteries in photovoltaic water pumping systems (PVWPS) presents some disadvantages, such as increased cost and reduction of efficiency [6] [7], and there are several studies cited in [8] [9] in which batteries are considered. A PVWPS in Oman incorporating a PV field with 840 W pk , no tank, and a 220 Ah lead-acid battery was the best solution analyzed after several simulations with HOMER [10].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative cost analysis of energy storage in tanks and batteries was carried out in PVWPS used in urban water pressurized networks, and it was found that the use of batteries was the most efficient alternative with the shortest payback periods [13]. The conclusions of a recent study comparing a PVWPS with a tank versus the battery storage solution indicated that the latter ensured access to domestic water in low-income rural areas at a lower cost [7]. The main drawbacks of the batteries identified in this study (with regular replacement, local recycling facilities, sustainable and efficient operation and maintenance) are related to the technology of the lead-acid batteries.…”
Section: Introductionmentioning
confidence: 99%
“…This is of paramount importance in Case A, where the great pumping operation hours need a great number of modules (reducing profitability). Some authors highlighted that the life-cycle cost of an optimised photovoltaic water pumping scheme with batteries is cheaper than embracing a tank as energy storage (Soenen et al 2021). But these authors highlight monetary conditions might decline if service managers do not keep maintenance and recycling.…”
Section: Discussion and Future Improvementsmentioning
confidence: 99%
“…The methods of external cost calculation show a trend of diversification [30]. However, factors such as discount rate, environmental impact category model, and regional differences have a great effect on LCC [45][46][47].…”
Section: Introductionmentioning
confidence: 99%